Enzyme Immobilization: Advancements, Techniques, and IndustrialApplications - Silva Lopes, Paulo Henrique; Nelson, David Lee; Damasceno, Sandra Matias (Current Enzyme Inhibition, 2025)
The text discusses the critical role of enzyme immobilization in enhancing the efficiency, reusability, and stability of biocatalysts in industrial applications. Immobilization techniques include covalent bonding, encapsulation, adsorption, and cross-linking, each with its unique advantages and challenges. Covalent bonding ensures strong, irreversible attachment of enzymes to supports, preventing leaching and maintaining enzyme stability under various conditions. Encapsulation protects enzymes within a semi-permeable matrix, preserving their activity while allowing access to substrates. Adsorption, relying on weak interactions, is simple and reversible but prone to enzyme leaching. Cross-linking involves intermolecular bonding between enzymes and supports, enhancing stability but potentially altering enzyme conformation. Selecting appropriate supports—organic or inorganic—is crucial to minimize enzyme deactivation and maintain activity. Organic supports, like chitosan and alginate, offer biocompatibility and sustainability, while inorganic supports, such as silica and metal oxides, provide robustness and high surface areas. The text highlights the significance of optimizing immobilization techniques for specific enzymes, considering factors like mechanical resistance, substrate diffusion, and compatibility with enzyme structures. Recent advancements include the development of novel supports like hybrid materials and the application of nanotechnology, which offers enhanced stability and catalytic properties. However, challenges like enzyme deactivation, activity loss over time, and high immobilization costs persist. The text emphasizes ongoing research to address these issues, aiming to improve the economic viability and efficiency of immobilized enzymes in industrial processes. The study underscores the importance of tailoring immobilization strategies to specific enzymes and applications, ensuring maximal catalytic performance and reusability.
Keywords: organic supports